PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL, ASIMETRI INFORMASI DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECURANGAN AKUNTANSI - Nazarah, Putri; Saleh, Muhammad (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
The purpose of this research is to examine the influence of effectiveness of internal control, information asymmetry and fidelity to accounting rules on accounting fraud. The population in this study is the regional work unit of Aceh Besar District, which the sampling technique uses non probability sampling with purposive sampling method. Respondents who are the object of this research are those who are most responsible for regional financial management consisting of the Head of Institution, Technical Activity Management Officer (PPTK) or Secretary and Head of Finance at 34 SKPD. Data analysis method used is multiple linear regression with the help of STATA 15. The result of this research shows that (1) effectiveness of internal controls, information asymmetry and fidelity to accounting rules has an effect on accounting fraud (2) ) effectiveness of internal controls has an effect on accounting fraud (3) information asymmetry has an effect on on accounting fraud and (3) fidelity to accounting rules has an effect on accounting fraud.